Interrogating the Ambivalence of Self-Fashioning and Redefining the Immigrant Identity in Bharati Mukherjeeâ€™s Jasmine - Banerjee, University of Wisconsin Milwaukee, USA, Suchismita (Asiatic: IIUM Journal of English Language and Literature, 2014)
Rejecting the paralysis of exilic consciousness, Bharati Mukherjee embraces the cultural diaspora of America to create a transformed identity of her own. Her psychological evolution is reflected in her fictional character, Jasmine, who, like her, subverts and participates in the hegemonic notion of immigrant identity and tries to carve out a different selfhood by participating in the violent process of decolonising the mind. However, the novel subverts this emancipatory rhetoric by creating ambiguous sites of identity performance where the protagonist is both complicit and resistant to the dominant culture. Analysis of these ambiguous sites in the novel would require us to consider the rhetoric of American â€œexceptionalismâ€ which makes the United States a unique, liberal, â€œredeemerâ€ nation, a place where individuals could carve out their identities through hard work, agency and determination. The aim of this paper is to apply the above rhetoric to explore the ambivalence of identity and subvert the notion of agency in Mukherjeeâ€™s diasporic novel, Jasmine (1989).